2004
DOI: 10.1097/01.smj.0000117795.47270.61
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Mortality of Patients Admitted to the Intensive Care Unit for Gastrointestinal Bleeding

Abstract: All-cause and GI bleeding-related 7-year mortality for patients admitted to the MICU with GI bleeding was lower than the rates cited in the literature. The Charlson score was helpful in predicting mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In our study, we reported mortality rate for a much shorter period of time (within 30 days). In another prospective cohort study of 66 patients admitted to intensive care units with a primary diagnosis of GI bleeding, Gopalswamy et al (27) reported that Charslon index correlated with long-term mortality (7 years). The Charlson index may be more accurate for long-term than short term mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we reported mortality rate for a much shorter period of time (within 30 days). In another prospective cohort study of 66 patients admitted to intensive care units with a primary diagnosis of GI bleeding, Gopalswamy et al (27) reported that Charslon index correlated with long-term mortality (7 years). The Charlson index may be more accurate for long-term than short term mortality.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, most of the mortality data in available studies are related either to in-hospital or 30-day mortality. 12 Higher mortality rates in patients with GI bleeding are attributed to associated comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, most of the mortality data in available studies are related either to in-hospital or 30-day mortality. 12 Higher mortality rates in patients with GI bleeding are attributed to associated comorbidities. 12 One study reported an overall mortality rate of ϳ14%, with these deaths occurring almost exclusively in older patients or those with serious comorbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Charlson Index, a global index of comorbidity derived from a cohort of general medical patients, [11] has been extensively used to assess comorbidities in different [12][13][14][15][16][17][18]. A modified Charlson Index (which removes the points for the CAD complications of myocardial infarction and heart failure from the original index) has been applied in patients with CAD [19].…”
Section: Introductionmentioning
confidence: 99%